(untitled) (Eurasian Journal of Engineering and Technology, 2022)
One of the most important national economic tasks is the modernization of the system of maintenance and repair of motor vehicles. This is largely facilitated by the widespread introduction of modern methods and means of technical diagnostics into the technological processes of maintenance (TO) and repair (R) of motor transport enterprises (ATP) and service stations (SRT).